PENGARUH KANDUNGAN INFORMASI LABA, ARUS KAS OPERASI, DAN ARUS KAS BEBAS TERHADAP CUMMULATIVE ABNORMAL RETURN (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2014-2015) - Dicky Yulian Anantha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to examine the factors influencing Cummulative Abnormal Return among manufacturing companies listed at Indonesian Stock Exchange 2014-2015. The factors constituting the control variables comprise of gross profit, operating cash flow, free cash flow, and firm size. The population covers 496 manufacturing companies listed at Indonesian Stock Exchange 2014, and 81 companies fulfilling the criteria are purposively selected as the research samples. The data are analyzed by linier regression method applying the SPSS version 24. The results of the analysis show that gross profit, operating cash flow, and firm size influence the Cummulative Abnormal Return. On the contrary, free cash flow variable has negative effect on Cummulative Abnormal Return.Keywords: Cummulative Abnormal Return, Gross Profit, Operating Cash Flow, Free